Myxobolus saladensis sp. nov., a new species of gill parasite of mugil liza (Osteichthyes, mugilidae) from samborombón bay, buenos aires, argentina - Marcotegui, Paula Soledad (2017)
Myxosporean Myxobolus saladensis sp. nov. in the gills of Mugil liza Valenciennes, 1836 from Samborombón Bay was described by light and electron microscopy studies. Spores were pyriform and binucleated, measuring 10.63±0.36 µm (n=20) long, 9.24±0.50 µm (n=20) wide and 4.13±0.36 µm (n=20) thick, included in polysporic cyst-like plasmodia. Elongated pyriform polar capsules were of equal size (3.84±0.27 µm long and 2.30±0.12 µm wide). The sporoplasm contained some sporoplasmosomes. Each PC contained a polar filament with 4-5 coils obliquely arranged in relation to the polar capsules axis. The PC wall was composed of two layers of different electron densities. Based on the morphological and ultrastructure differences of the spore to those of previously described species of Myxobolus, we describe a new species, Myxobolus saladensis sp. nov.